Pelatihan Implementasi Proyek Penguatan Profil Pelajar Pancasila bagi Guru Sekolah Dasar - Dini Ramadhani; Ary Kiswanto Kenedi; Muhammad Febri Rafli; Hanif Harahap; Via Mega Ananda Banjar Negara; Riska Hayati; Atika Ulya Akmal (Majalah Ilmiah UPI YPTK, 2023)
Dini Ramadhani, Ary Kiswanto Kenedi, Muhammad Febri Rafli, Hanif Harahap, Via Mega Ananda Banjar Negara, Riska Hayati, Atika Ulya Akmal The project to strengthen the profile of Pancasila students is a form developed by the Indonesian Ministry to develop a profile of Pancasila students. The project to strengthen the profile of Pancasila students is an integral part of the independent curriculum so that the project to strengthen the profile of Pancasila students must be mastered by elementary school teachers so that it can be applied to the learning process and the achievement of predetermined educational goals. Based on fact, it was stated that the ability of elementary school teachers was still low in compiling independent curriculum learning tools and the low ability of elementary school teachers in implementing projects to strengthen the profile of Pancasila students. The purpose is to improve the ability of elementary school teachers to develop independent curriculum learning tools and to improve the ability of elementary school teachers to implement projects to strengthen the profile of Pancasila students. The participants were elementary school teachers in cluster IV Cut Mutia, Langsa, totaling 30 people. The method is training. The material presented is the development of independent curriculum tools and training in implementing the Pancasila student profile strengthening project. The results stated that teachers had been able to develop independent curriculum learning tools and implement projects to strengthen the profile of Pancasila students. The implications of this dedication can be used as an effort to develop teachers' abilities in compiling curriculum learning tools and implementing projects to strengthen the profile of Pancasila students in elementary schools